Implementation of the Protocol for Recovering Bodies for Patients Indicated by Covid-19 at Bhakti Wira Tamtama Hospital Based on Legislation - Lesmana, Asep Yogi Kristiawan; Yustina, Endang Wahyati; Hartini, Inge (Universitas Katolik Soegijapranata Semarang, 2022)
Abstract: The importance of the protocol for returning bodies to hospitals related to the Covid-19 pandemic requires that all hospitals in Indonesia implement standard operating procedures for returning bodies. One of the hospitals that implements this is the Bhakti Wira Tamtama Hospital. The problem that often occurs is that the family refuses to process the body according to the protocol for returning the bodies of Covid-19The purpose of this study was to get an overview of the arrangements and implementation as well as the factors that influence the process of returning the bodies at the Bhakti Wira Tamtama Hospital in Semarang. The research method uses qualitative research. Primary data was taken from direct interviews with informants, namely the person in charge of the installation and the corpse handling officer.The policy for returning the bodies of Covid-19 patients at Bhakti Wira Tamtama Hospital is carried out in accordance with the Standard Operating Procedures (SPO), which consists of the preparation stage, the process of returning the bodies, to the handing over of the bodies. The juridical factor is that there are no specific regulations governing the disposal of bodies from probable, suspected or confirmed cases. Bhakti Wira Tamtama Semarang Hospital experienced difficulties in terms of providing education to the family. The sociological factor is that the family refuses if the body is recovered at the hospital. Barriers to technical factors at the Bhakti Wira Tamtama Hospital were the knowledge of the officers who were not optimal and the availability of inadequate infrastructure, as well as the limited PPE when the pandemic began to hit Indonesia.Keywords: Protocol, Retrieval of Bodies, Covid-19, Hospital, Laws and Regulations. Abstrak: Pentingnya protokol pemulasaran jenazah di rumah sakit terkait pandemi covid-19 mewajibkan untuk seluruh rumah sakit yang ada di Indonesia menerapkan standar operasional prosedur pemulasaran jenazah. Salah satu rumah sakit yang menerapkan hal tersebut yaitu rumah sakit Bhakti Wira Tamtama. Permasalahan yang sering terjadi yaitu keluarga menolak proses pengurusan jenazah dilakukan sesuai protokol pemulasaran jenazah covid-19Tujuan penelitian ini untuk mendapatkan gambaran pengaturan dan pelaksanaan serta faktor-faktor yang mempengaruhi proses pemulasaran jenazah di Rumah Sakit Bhakti Wira Tamtama Semarang. Metode penelitian menggunakan penelitian kualitatif. Data primer diambil dari wawancara langsung dengan narasumber yaitu penanggung jawab instalasi dan petugas pemulasaran jenazah dan.Kebijakan pemulasaran jenazah pasien Covid-19 di RS Bhakti Wira Tamtama dilakukan sesuai Standar Prosedur Operasional (SPO) yang terdiri dari tahap persiapan, proses pemulasaran jenazah, hingga penyerahan jenazah. Faktor yuridis yaitu belum ada peraturan khusus mengatur tentang pemulasaran jenazah dari kasus probable, suspek, maupun terkonfirmasi. RS Bhakti Wira Tamtama Semarang mengalami kesulitan dalam hal memberikan edukasi kepada pihak keluarga. Faktor sosiologis yaitu pihak keluarga menolak jika jenazah dilakukan pemulasaran di rumah sakit. Hambatan faktor teknis di RS Bhakti Wira Tamtama berupa pengetahuan dari petugas yang belum maksimal dan ketersediaan sarana prasarana yang kurang memadai, serta keterbatasan APD pada saat pendemi mulai melanda Indonesia.Kata kunci : Protokol, Pemulasaran Jenazah, Covid-19, Rumah Sakit, Peraturan Perundang-undangan.